Allah Setia Dalam Memenuhi Janjinya Tafsir Kitab Yosua 21:43-45 - Agnes Putri Banurea; Sufriadi Situmorang (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
The title of Joshua chapter 21:43-45 is “God is Faithful to His Promises”. Is “God is Faithful in Fulfilling His Promises.” In these verses, God shows His faithfulness by giving the Israelites all of In these verses, God shows His faithfulness by giving the Israelites the entire land of Canaan, as He promised to their forefathers. the land of Canaan, just as He promised to their ancestors. Faithfulness God's faithfulness is evident in the fulfillment of His promises, which includes giving the land to His people so that their enemies can be protected. His people so that their enemies could not stand against them; this shows that God not only promises, but shows that God not only promises, but also actively carries out His promises. Carry out His promises. This verse, however, also reminds us that the people's obedience to God's covenant is essential to fully enjoy the blessings, to the fullest. God's faithfulness in fulfilling His promises gives hope to every believer. Every believer. As such, Joshua 21:43-45 invites us to believe and live in obedience, while waiting for the fulfillment of God's promises in our lives. promises in our lives.